Sir Arthur Bliss’s Music Things to Come (1936): A Study of Contemporaneous Sources and Musical Materials - Snedden, Nicol William (Journal of Film Music, 2014)
At the invitation of H. G. Wells, Sir Arthur Bliss composed his first and most famous film score, Things to Come, over the period 1934–35. Wells had full artistic control over the film and insisted on the music being composed before shooting commenced. Recording the majority of the score in advance was highly irregular in terms of the musical practice adopted, and it is clear many modifications were made in order to fit the music to the film. Six months in advance of the film premiere, Bliss performed his Suite from Film Music during the 1935 BBC Proms season. Primary source materials related to the music are analyzed, including newly found 78 rpm records made by Bliss and a Denham Film Studios playback recording titled “Utopian Hymn.” Bliss’s landmark score is lost except for “No. 9 Attack on Moon Gun,” preserved at Cambridge University Library.